1976
DOI: 10.2172/7267133
|View full text |Cite
|
Sign up to set email alerts
|

High explosive characterization for the dice throw event

Abstract: NOTICE 'lbu report \y.s prepared IS an m o u n t or work wnared by the United S U t u Gomnmcnt. Ncilhci the United S U t u nor the United Slate Energy Research and Development Administration. nor m y 01 their employees, nor any d their mntmtors. subcontractan. or their employm. m k u m y warranty. cxpreu or implied. or assumes any 1 4 liability or rcrpondbilily for the aecuncy, completenen or urfulnen of m y informtian. ~PPU.IYI. product 01 pmrrrr disclaud. or represents that its use would not infringe private… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The deviation of the higher-order DSD size-effect curves from the data at larger HE dimensions is due to the value of D CJ = 5.2 km s −1 used in the calibration of the higher-order DSD relation (Bdzil et al 2002). This was obtained from an extrapolation based on the 'dice throw' series of large-scale ANFO tests (Helm et al 1976). Subsequent analysis by Bdzil (2008, personal communication) of the more carefully controlled ANFO rate-stick test series (Bdzil et al 2002) led to the recommendation to lower D CJ to 4.8 km s −1 , as used by Bdzil (2008, personal communication) in the calibration of the lower-order D n -κ form of the DSD relation for ANFO (table 9).…”
Section: Comparison Of Dsd Predictions With Slab and Rate-stick Expermentioning
confidence: 99%
“…The deviation of the higher-order DSD size-effect curves from the data at larger HE dimensions is due to the value of D CJ = 5.2 km s −1 used in the calibration of the higher-order DSD relation (Bdzil et al 2002). This was obtained from an extrapolation based on the 'dice throw' series of large-scale ANFO tests (Helm et al 1976). Subsequent analysis by Bdzil (2008, personal communication) of the more carefully controlled ANFO rate-stick test series (Bdzil et al 2002) led to the recommendation to lower D CJ to 4.8 km s −1 , as used by Bdzil (2008, personal communication) in the calibration of the lower-order D n -κ form of the DSD relation for ANFO (table 9).…”
Section: Comparison Of Dsd Predictions With Slab and Rate-stick Expermentioning
confidence: 99%
“…The Cheetah JWL assumes that reactions go to equilibrium, and has about 25% more energy than Ref. 2. This suggests that reaction also persists at 11.5-inch diameter-and perhaps for all laboratory-scale configurations.…”
Section: Eos Analysismentioning
confidence: 99%
“…For non-ideal explosives such as ANFO, the standard cylinder is too small compared to the reaction zone, and must be scaled up accordingly. Previous ANFO cylinder tests 2 were conducted at diameters up to 292.1 mm (11.5 inches). It was reported that a test diameter of 101.6 mm (4 inches) was the minimum size to scale favorably with the large cylinder test; yet, very large field experiments 3 yielded somewhat higher det-onation velocities and pressures than even the largest cylinder test.…”
Section: Introductionmentioning
confidence: 99%